Characteristics and Risk Factors of Workplace Violence: Experiences of Urologists Working in Turkey - Germiyanoğlu, Rüştü Cankon; Demir, Demirhan Örsan; Kaçan, Turgay (Urology (Ridgewood, N.J.), 2024)
To investigate how safe urologists feel in their work environment and the sociodemographic characteristics and working conditions that affect their sense of security. The study was conducted with urologists working in different hospitals. Data were collected through a 2-part online survey that took a few minutes to complete. The first section included items about the participant’s sociodemographic characteristics and working conditions. The second part consisted of the Safety and Confidence Scale for Health Professionals (SCSHP) to assess how safe the physicians feel when faced with violence and how confident they are in handling violence. The study included 221 participants. Male urologists had a higher median SCSHP score than female urologists (P <.001). Single urologists felt safer when faced with violence than those who were married (P = .037). Participants who worked in hospitals with 24-hour security or law enforcement presence also felt safer than those who did not. Urologists who worked at universities and those who were faculty members also had higher SCSHP scores than urologists working in secondary and tertiary care (P <.001 for both). When SCSHP scores were compared according to professional experience, we observed that urologists in the first year of practice felt safer, while there was no statistically significant difference between the other groups. Among urologists, those who feel least safe from workplace violence are female urologists, those who work in secondary and tertiary hospitals, and those who do not have 24-hour security or law enforcement in their center.